Estudo da estabilidade e avaliação do efeito do extrato de chá verde (Camellia sinensis) microencapsulado em modelo experimental de lesão gástrica induzida por etanol em camundongos - Silva, Francisca Mayla Rodrigues (2020)
Among the constituents of green tea (Camellia sinensis), phenolic compounds and caffeine stand out, which have been associated with various biological activities in the body. These compounds may present instability in light and oxygen conditions, causing loss of bioactive properties. This work aimed to obtain scientific evidence of the encapsulation power of green tea extract, evaluating the stability of microcapsules and studying their functional effect and action in an experimental model of gastric lesion induced by ethanol in mice. The green tea extract (ECV) was obtained from leaves immersed in 75% ethanol using an ultrasonic bath. The green tea extract microcapsule (MECV) was obtained by atomization using ECV as the core material and cashew gum and maltodextrin as the wall material. The microcapsules showed lower values of humidity (1,42%), hygroscopicity (3,66%) and water activity (0,36) when compared to the pure extract, demonstrating that the encapsulation helps in increasing the life of the extract. The MECV sample was characterized as being of greater luminosity (L* = 77,94), less intensity of the red color (a* = 0,84) and greater intensity of the yellow color (b* = 23,80). The stability study demonstrated the feasibility of using MECV, since better results were found in maintaining the total extractable polyphenols and the antioxidant activity, as well as greater maintenance of moisture, water activity and color evaluated during the storage period of 75 days. High levels of total phenolic compounds and total antioxidant capacity were obtained for the MECV sample with values of 14964,4 mg/100g and 1187,4 μM of Trolox.g-1, respectively, demonstrating the potential to be explored from the MECV sample as source of compounds of interest. It has been shown that MECV provides greater bioavailability of total extractable polyphenols (28,2%) and total antioxidant activity (24,2%) when compared to the ECV sample, and its daily intake may provide positive health results. The ECV and MECV samples did not show larvicidal activity at the concentrations evaluated against Artemia salina, did not present toxicity at the concentrations tested against adult Zebrafish and did not present cytotoxicity for the studied human epithelial cells, being considered safe samples and possible use as an additive in new products. ECV and MECV (10 mg/kg) provided greater protection of the gastric mucosa of the treated animals, reducing gastric damage caused by the administration of ethanolabs, as well as promoting an increase in GSH levels and a reduction in MDA levels, indicating antioxidant action reducing possibility of tissue lipid peroxidation. In this way, the potential for the food industry of the use of microparticles as an alternative to increase the stability of the 11 compounds of interest present in the green tea extract is verified, in addition to providing a food ingredient whose daily intake brings positive health results.